2009
DOI: 10.1111/j.1471-4159.2009.05899.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of endogenous interleukin‐10 enhances secondary inflammatory process after spinal cord compression injury in mice

Abstract: Interleukin‐10 (IL‐10) exerts a wide spectrum of regulatory activities in the immune and inflammatory response. The aim of this study was to investigate the role of endogenous IL‐10 on the modulation of the secondary events in mice subjected to spinal cord injury induced by the application of vascular clips (force of 24 g) to the dura via a four‐level T5–T8 laminectomy. IL‐10 wild‐type mice developed severe spinal cord damage characterized by oedema, tissue damage and apoptosis (measured by Annexin‐V, terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 50 publications
3
65
0
Order By: Relevance
“…Th2 cells promote facial motoneuron survival after facial nerve axotomy, but a reduced survival rate has been reported in IL-4 knock-out mice (Deboy et al, 2006). More severe secondary inflammatory responses have been reported in IL-10 knock-out mice, resulting in worse functional recovery after spinal cord compression (Genovese et al, 2009). Moreover, treatment of contused rat spinal cords with IL-10 reportedly improves motor function recovery (Bethea et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Th2 cells promote facial motoneuron survival after facial nerve axotomy, but a reduced survival rate has been reported in IL-4 knock-out mice (Deboy et al, 2006). More severe secondary inflammatory responses have been reported in IL-10 knock-out mice, resulting in worse functional recovery after spinal cord compression (Genovese et al, 2009). Moreover, treatment of contused rat spinal cords with IL-10 reportedly improves motor function recovery (Bethea et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to in vitro studies, increased NF-κB binding activity in the spinal cord has been reported in vivo after compression SCI [103] and increased levels of TNF are observed in the spinal cords of Nrf2-deficient mice [97,103] . Due to its relatively specific cytotoxicity towards oligodendrocytes, TNF may be one of the main factors responsible for the damage of these cells and pronounced demyelination after SCI [104][105][106] .…”
Section: Sci Induces Death Of Neuronal and Glial Cells As Well As Inmentioning
confidence: 99%
“…The secondary injury is mediated by multiple injury processes, including inflammation, free radical-induced cell death, and glutamate excitotoxicity [7]. Inflammatory response contributes a lot in the regulation of SCI pathogenesis, and seems to play a pivotal role in nerve injury and regenerative response [8]. In addition, inflammatory response may contribute to the apoptosis of neurons and oligodendrocytes as well as to the loss of neuronal function [9].…”
Section: Original Papermentioning
confidence: 99%